Technical Creativity and Free Schematism - Cecchi, Dario (Aesthetica Preprint, 2022)
The post-phenomenological philosophy of technics (Derrida, Ferraris, Stiegler) emphasizes the character of supplement in the technical devices: these devices anticipate the human experience. An example are the technologies of archiving, which create ‘hypomneses’ of memory. A similar argument is argued about the historicity of perception (Benjamin, Kittler). Technical devices seem to configure a technological a priori, whose transcendental character lies still problematic, insofar as it precedes the constitution of a subjectivity. Emilio Garroni’s aesthetic reflection can be put in dialogue with the philosophy of technics, in order to find possible solutions. His reading of the free play of the imagination with the understanding, in Immagine Linguaggio Figura (2005), foreshadows a ‘free schematism’, which is not bound to the aesthetic experience, and is prior to the objective schematism at work in cognition narrowly construed. This free schematism can be reconsidered in a techno-aesthetical key (Montani), as a way of experimenting the differentiation of the sensibility, which is produced by a technical performance. One could so recognize in it a creative trend oriented to develop or follow a series of rules, without being defined by any logic of control (Velotti). This hypothesis can be linked to the idea of an anthropological function of art, exposed in the essay Creativity (1978). Garroni states here that, in front of a potentially unlimited opening of the solutions available to the problem of the adaptation, which is offered to homo sapiens by their predominantly metaoperative creativity, art seems to promote a sort of paradoxical adaptation to a never accomplished adaptability, so that the anxiety engendered by the uncontrollability of technics may become highly meaningful.